Factors that influence repurchase intention for RON 92 fuel products - Mohamad Arfi Arnum; Dita Puruwita; Terrylina Arvinta Monoarfa (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study aims to determine the effect of perceived value, trust, and WOM on repurchase intention on RON 92 fuel products. The sampling method used was purposive sampling with the criteria of domiciled in the DKI Jakarta area, aged at least 17 years and using Pertamax in the last three months. The number of samples in this study was 212 respondents. The analysis method used SEM (Structural Equation Modeling) using AMOS software. The results showed that perceived value and trust have a positive and significant influence on WOM and repurchase intention. However, WOM does not have a significant influence on repurchase intention on RON 92 fuel products.